Effects of tibolone or continuous combined oestradiol and norethisterone acetate on lipids, high‐density lipoprotein subfractions and apolipoproteins in postmenopausal women in a two‐year, randomized, double‐blind, placebo‐controlled trial. (28th January 2020) - Kotecha, Payal Trupti; Godsland, Ian F.; Crook, David; Stevenson, John C.
Abstract: Objective: To compare the effects of (a) tibolone, (b) continuous combined oestrogen plus progestogen and (c) placebo on plasma lipid and lipoprotein markers of cardiovascular risk in healthy postmenopausal women. Study design: Randomized, single‐centre, placebo‐controlled, double‐blind study. Patients: One hundred and one postmenopausal women were randomized (1:1:1) into one of three groups taking daily 2.5 mg tibolone, continuous oral oestradiol‐17β 2 mg plus norethisterone acetate 1 mg daily (E2 /NETA) or placebo. Main outcome measures: Fasting serum lipid, lipoprotein and apolipoprotein concentrations measured at baseline and after 6, 12 and 24 months of treatment. Results: Both tibolone and E2 /NETA lowered plasma total cholesterol concentrations relative to placebo. With tibolone, high‐density lipoprotein cholesterol (HDL‐C) was reduced (−27% at 24 months, P  < .001), the greatest effect being in the cholesterol‐enriched HDL2 subfraction (−40%, P  < .001). Tibolone's effect on HDL concentrations was also apparent in the principal HDL protein component, apolipoprotein AI (−29% at 24 months, P  < .001). However, there was no significant effect of tibolone on low‐density or very low‐density lipoprotein cholesterol (LDL‐C and VLDL‐C, respectively). By contrast, the greatest reduction in cholesterol with E2 /NETA was in LDL‐C (−22% at 24 months, P  = .008). E2 /NETA reduced HDL‐C to a lesser extent than tibolone (−12% at 24 months, P  < .001). Effects on HDL apolipoproteins were similarly diminished relative to tibolone. E2 /NETA had no effect on VLDL‐C or on the protein component of LDL, apolipoprotein B. Conclusion: Tibolone reduces serum HDL. E2 /NETA reduces LDL cholesterol but not apolipoprotein B, suggesting decreased cholesterol loading of LDL. Any impact these changes may have on CVD risk needs further investigation.